Design And Development Of Engine Control System For Advanced Diesel Engine Research - Edmund, Ung Eng Soon (Universiti Sains Malaysia, 2021)
Diesel engines are one of the most energy efficient and most used engines in the industry today. With the global concern on energy crisis and rising pollution levels, new diesel engines should be researched and designed to be more environmentally friendly as well as having increased engine performance. In the Mechanical School of Universiti Sains Malaysia, the existing research engine equipment were upgraded to be able to facilitate advanced diesel engine tests such as different biodiesel fuels, intake air supply control and split injection strategies. Therefore, various systems have been implemented into the existing research engine including the electrical signal throttle control, throttle valve control, EGR valve control and OBD data acquisition system. On top of that, a fully integrated control panel is designed to control and display data of all newly installed systems as well as the existing systems on the testbench. Results shows that the newly installed systems were working smoothly with very little to no errors. This project is a first step in developing a fully capable research engine to test out various other parameters regarding sustainability on the diesel engine.